Novel Approaches Towards Designing of Isoform-Selective Inhibitors Against Class II Histone Deacetylases: The Acute Requirement for Targetted Anticancer Therapy - Ahmad Ganai, Shabir (Current Topics in Medicinal Chemistry, 2016)
Histone deacetylases (HDACs) regulate gene expression by modulating chromatin architecture via histone hypoacetylation. They play a key role in regulating cellular processes including cell cycle arrest and apoptosis. Hyperactivity of HDACs plays a key role in tumour onset and progression making these enzymes as striking targets for anticancer drugs and therapy. Certain cancers are associated with upregulation of specific class II HDAC isoform rather than multiple ones. Therapeutic intervention using small-molecules namely histone deacetylase inhibitors (HDACi), often targets many isoforms unselectively (pan-HDACi) due to structural identity culminating in debilitating off-target effects and reduced in vivo potency. This emphasizes the escalating need for developing isoform-selective inhibitors against the defined class of HDACs. Despite the safe and elevated therapeutic benefit, the design of such inhibitors has been challenging. The present article provides intricate details about the role of class II HDAC isoforms in fuelling distinct cancers and the current challenges with the use of pan-HDAC inhibitors in anticancer therapy. The article also highlights the diverse synthetic and in silico approaches taken by scientific community towards the designing of isoform-selective inhibitors against class II HDAC isoforms. The strategies discussed in this review will provide further impetus to the ongoing research regarding the designing of isoform-selective inhibitors for safe and effective anticancer therapy which is today’s need.
Keywords: Isoform-selective inhibitors